DIGITAL READINESS, DIGITAL LEADERSHIP, AND ORGANIZATIONAL CAPABILITIES AS DRIVERS OF ORGANIZATIONAL PERFORMANCE: EVIDENCE FROM THE BROADCASTING INDUSTRY - Ashisyah Meitul Kholidiah; Dhiyan Septa Wihara (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study investigates how digital readiness, digital leadership, and organizational capability affect organizational performance at JTV East Java. As regional broadcasters confront rapid digital disruption, it is essential to understand how readiness, leadership, and internal capabilities together shape performance outcomes—an area that remains underexamined in the Indonesian broadcasting context.METHODOLOGY - This study used a survey with a quantitative explanatory design to identify factors affecting organizational performance. A 24-item online questionnaire yielded 105 valid responses from 118 JTV East Java employees (an 89% response rate). Instrument validity and reliability were established using Pearson’s r (r = 0.190) and a Cronbach’s alpha above 0.60. Before performing multiple linear regression in SPSS version 27, standard assumption checks for normality, heteroscedasticity, and multicollinearity were performed to confirm the data were suitable for analysis.FINDING - All three variables partially influence Organizational Performance positively and significantly: Digital Readiness (t = 4.378; p < 0.001; β = 0.393) is the most dominant predictor, followed by Organizational Capability (t = 3.348; p = 0.001) and Digital Leadership (t = 2.911; p = 0.004). Simultaneously, the three variables explain 82.3% of the variance in Organizational Performance (F = 156.715; p < 0.001; R² = 0.823). These findings imply that JTV East Java should prioritize investments in digital infrastructure, cultivate digital leadership, and strengthen organizational adaptive capabilities to sustain performance amid ongoing digital transformation in the broadcasting industry.